Clinical and Genetic Varieties of Gaucher Disease in Iraqi Children - Ibraheem, Mohammad Fadhil; Ahmed, Shaymaa Jamal (Journal of Child Science, 2020)
Gaucher disease (GD), which is due to a deficiency in the lysosomal enzyme β-glucocerebrosidase, is a rare genetic disorder. It is characterized by a wide variety of clinical manifestations and severity of symptoms, making it difficult to manage. A cross-sectional hospital-based genetic study was undertaken with 32 pediatric patients. We recruited 21 males and 11 females diagnosed with GD, with a male-to-female ratio of 1.91:1. The mean age of the study population was 8.79 ± 4.37 years with an age range from 8 months to 17 years. We included patients on clinical evaluation from 2011 to 2019. An enzyme assay test was used to measure β-glucosidase enzyme activity in leukocytes and the GBA gene study was performed by polymerase chain reaction technique. We found GD type 1 in 27 (84.37%) participants, GD type 3 in five (15.63%) participants, while none classified as GD type 2. The dominant mutation in GD 1 was N370S in 81.5%, of which two-thirds were homozygous. The second common mutation in this type of disease (L444P) was present in nine cases (40.9%), two of whom were homozygous (9.9%). Meanwhile, R463C was present in six cases (27.27%), of whom one was homozygous. In GD 3, the dominant mutation was L444P as seen in 80% of the patients followed by N370S and R463C in 20%. This study shows that the most common mutant allele in this study was N370S, followed by L444P. Further large-scale studies with more advanced designs are recommended to explore the sequences of GBA genes.
Keywords: Gaucher disease; N370S; L444P; R463C; GBA genes